2020
DOI: 10.3390/cells9102175
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome and Proteome Analyses Reveal the Regulatory Role of miR-146a in Human Limbal Epithelium via Notch Signaling

Abstract: MiR-146a is upregulated in the stem cell-enriched limbal region vs. central human cornea and can mediate corneal epithelial wound healing. The aim of this study was to identify miR-146a targets in human primary limbal epithelial cells (LECs) using genomic and proteomic analyses. RNA-seq combined with quantitative proteomics based on multiplexed isobaric tandem mass tag labeling was performed in LECs transfected with miR-146a mimic vs. mimic control. Western blot and immunostaining were used to confirm the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…However, the effect of miR-146a wound healing remains uncertain. Poe et al has reported that several identified miR-146a-targeted pathways are important for corneal epithelial homeostasis, such as EGFR, Notch, anchoring junctions, adherens junctions, TGF-β and inflammation-related signaling 49 . Our present study shows a negative feedback regulation of miR-146a on NF-κB activation and its downstream secreted inflammatory cytokines via IRAK1 and TRAF6 in HCECs, suggesting a potential therapeutic effect on controlling inflammation during DED.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of miR-146a wound healing remains uncertain. Poe et al has reported that several identified miR-146a-targeted pathways are important for corneal epithelial homeostasis, such as EGFR, Notch, anchoring junctions, adherens junctions, TGF-β and inflammation-related signaling 49 . Our present study shows a negative feedback regulation of miR-146a on NF-κB activation and its downstream secreted inflammatory cytokines via IRAK1 and TRAF6 in HCECs, suggesting a potential therapeutic effect on controlling inflammation during DED.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-146a was found hyper-expressed in patients with Sjogren’s syndrome, a condition characterized by dry eye, and in Sjogren-prone mice as well [ 40 , 41 ]. In addition, Movahedan et al [ 42 ] described a Notch1 -mediated decrease in early-stage corneal wound healing, and a recent study by using human primary limbal epithelial cells [ 43 ] demonstrated that miR-146a increased Notch 1 by Numb downregulation. In accordance, both Targetscan human v7.2 ( ; accessed 6 October 2021) and miRDB ( ; accessed 6 October 2021) databases report miR-146a-5p/ Numb interaction, and previous studies on other cell types demonstrated the miR-146a-mediated Numb downregulation as well [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the insertion of specific miRNAs has been shown to promote corneal regeneration by increasing the expression of c-MET and inhibiting that of cathepsin F and MMP-10, thus accelerating tissue healing in diabetic patients [ 118 ]. In addition, miRNA 146-α can modulate corneal regeneration and stem reservoir maintenance [ 119 , 120 ] and it has been shown that its overexpression can alter normal repair functions in diabetic corneas [ 121 , 122 ]. The main studies regarding the role of miRNAs in corneal regeneration are summarized in Table 2 .…”
Section: Subcellular Therapiesmentioning
confidence: 99%